Pengaruh Word of Mouth, Perceived Value, dan Harga terhadap Minat Beli Ulang Mixue di Kota Medan : Penelitian - Muhammad Zaki Hanafia NST; Hafiza Adlina; Onan Marakali Siregar (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2026)
This study aims to analyze the effect of word of mouth, perceived value, and price on the repurchase intention of Mixue products in Medan City. This research employs a quantitative method with an associative approach to examine the relationships and influences among variables. The sampling technique used was purposive sampling, involving 96 respondents who were consumers of Mixue in Medan City and had made at least one purchase. Primary data were collected through the direct distribution of questionnaires, while secondary data were obtained from literature reviews. The data analysis methods included validity testing, reliability testing, classical assumption testing, multiple linear regression analysis, and hypothesis testing through partial tests (t-test), simultaneous tests (F-test), and the coefficient of determination. The results indicate that word of mouth, perceived value, and price have a positive and significant effect on Mixue’s repurchase intention in Medan City, both partially and simultaneously. The adjusted R-square value of 0.967 indicates that 96.7% of the variation in repurchase intention can be explained by these three variables, while the remaining 3.3% is influenced by other factors not examined in this study. These findings suggest that recommendation-based marketing strategies, consumers’ perceived value, and competitive pricing play an important role in increasing consumers’ repurchase intention toward Mixue.